2003
DOI: 10.3402/fnr.v47i3.1482
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin B12, folate, homocysteine and cognition in the elderly

Abstract: Normal and subnormal serum levels of vitamin B 12 and/or folate do not exclude functional deficiency, and elderly people are specifically exposed to deficiency owing to impaired nutrition, malabsorption, accompanying diseases and current medication. Several studies report that low levels of vitamin B 12 are more common in people with Alzheimer's disease (AD) than in non-demented people. Low levels of folate are also correlated with other types of dementia. Current studies suggest that low levels of vitamin B 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Were such a programme implemented, there would be fewer patients with low serum B 12 and biochemically defined B 12 deficiency for clinicians to investigate. Several studies have reported that adults with suboptimal B 12 status have poorer cognitive functioning or could improve with supplementation(30-32). However, results from other B-vitamin supplement trials have failed to yield clinically measurable benefit(33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Were such a programme implemented, there would be fewer patients with low serum B 12 and biochemically defined B 12 deficiency for clinicians to investigate. Several studies have reported that adults with suboptimal B 12 status have poorer cognitive functioning or could improve with supplementation(30-32). However, results from other B-vitamin supplement trials have failed to yield clinically measurable benefit(33,34).…”
Section: Discussionmentioning
confidence: 99%